Managing Halal Certification Supply Chain: Determinants Success Factors Framework for a Hotel Performance - Mohd Rizal Razalli (International Journal of Supply Chain Management, 2018)
Muslims are obliged to follow Shariah Laws which require them to consume the Halal food and products. One of the ways to authenticate the Halalness of food is through the Halal certification. This certification system can guide Muslims in making decision for certain products and services without hesitation. Because of the demand for halal products and services is very promising, more and more companies are starting to certify their products and services. This demand is also true to one of the largest Malaysias contributors to the national economy - hotel industry. The Halal certified food can give an extra edge to the industry in luring not only the local tourists but also the international tourists as well. Despite the increase in demand for certification, the statistics released by JAKIM in 2017 showed that there were only 442 certified Halal hotel out of 4661 hotels in Malaysia. This could be due to numerous challenges faced by companies in obtaining the certification. One of the main challenges of obtaining the certification is due to the lack of understanding of the Halal certification process itself. Hence, this paper attempts to introduce a determinant success factors framework of Halal certification supply chain related to the hotel industry. A quantitative study was adopted to achieve the objective. The findings revealed the determinants factors. This framework can be used for hotels to improve their understanding as well as their initiatives in obtaining the Halal certification.